Solid Variant of Alveolar Rhabdomyosarcoma of Nasal Cavity - Bhattarai, A; Shrestha, BL; Dhakal, A (Kathmandu University Medical Journal, 2020)
Rhabdomyosarcoma comprises about half of the soft tissue tumors. Approximately 40% of the alveolar subtype occur in the head and neck region. Patients present with unilateral nasal mass with/without lymphadenopathy and with/without orbital manifestations. Diagnosis is aided radiologically by CT scan, MRI along with biopsy and is confirmed by immunohistochemistry. Treatment involves surgical resection, chemotherapy, radiotherapy or a combination of these. In spite of treatments, however, the outcome is poor. This is a case report of 14-year-old male who presented with unilateral nasal mass with proptosis of right eye who was eventually diagnosed as a case of alveolar rhabdomyosarcoma of solid variant.